Satisfaction among Malacca's General Hospital nurses / Maizatul Eliana Mansor , Mira Adilah Zakariah and Siti Nur Ain Kamal - Mansor, Maizatul Eliana; Zakariah, Mira Adilah; Kamal, Siti Nur Ain (Faculty of Office Management and Technology, 2012)
The purpose of this study is to examine the relationships between job satisfaction and job burnout. The study focused on nurses who work at Malacca's General Hospital. The respondent of this study were those nurses who are currently working at Malacca's General Hospital. Questionnaires were used as method of collecting data. Out of 92 questionnaires distributed, only 64 were returned. Results showed grief to have significant correlations; negative with burnout, positive with job satisfaction. It seems that despite the scope of literature job satisfaction and burnout, the empirical evidence does not yet provide the nursing profession with a cogent conceptual framework in fully understanding and explaining the antecedents, consequences, and process involved in job satisfaction and job burnout among nurses. Therefore, further study should be conducted in order to identify whether Malaysian nurses as a whole were satisfied with their work and they do not feel burnout.